(untitled) (Investigación + Acción, 2025)
The purpose of this interview is to gain insight into Extension Projects from the perspective of extension practitioners. To this end, we are interested in learning about these projects from an institutional standpoint—objectives, territorial partnerships, and expected outcomes—from the perspective of the teams involved.